ROLE OF EFFECTIVE MICROORGANISMS (EM) IN WASTE WATER TREATMENT AND THEIR EFFECT ON THE GROWTH PARAMETERS AND YIELD OF VIGNA MUNGO LINN. IN THE KLT SERIES OF THIRUVARUR DT, TAMILNADU, INDIA - J.VICTORIA,; N.UMA MAHESWARI, (International Journal of Pharma and Bio Sciences, 2016)
A study on the determination of the use of Effective Microorganisms (EM) was carried out. EM was purchased from the office of ‘Ecopro’ Auroville, Auroshilpam, Tamilnadu, India. The waste water was from STET Women’s College, Sundarakkottai, Mannargudi (Tk), Thiruvarur (Dt). The parameters that indicate the waste water treatment process such as odour, pH, DO, BOD, COD, TDS, TS, TSS, Nitrate and Phosphate were determined before and after the treatment of wastewater, to observe the efficiency of selected process. There was an appreciable reduction in the all the parameters. The parameters showed an elevated level in the raw sewage but after treatment there was a steady reduction after 5, 10, 15 and 20 days of incubation. No reduction was observed in the level of DO. All the parameters were reduced to tolerable environmental standard. The treated waste water was reused for the cultivation of the secondary crop,Vigna mungo. Soil samples were collected from the village Vangathangudi, Thiruvarur District, Tamilnadu, India which consists of Kalathur (Klt) soil series, one of the major soil series of Thiruvarur District. The experimental set up was designed as T1-EM alone, T2- treated waste water, T3-EM plus EM treated waste water and C-control.T3 showed the highest results in all the growth parameters and yield of the plant.